Effects of Leucaena biochar addition on crop productivity in degraded tropical soils. (November 2020) - Elias, Dafydd M.O.; Ooi, Gin Teng; Ahmad Razi, Mohammad Fadhil; Robinson, Samuel; Whitaker, Jeanette; McNamara, Niall P.
Abstract: Biochar has the potential to increase crop yields on degraded, tropical soils. It can be readily produced in rural community settings using low-cost technology and is most economically feasible if produced from local biomass or waste residues. Biochar was produced from Leucaena biomass using low-cost pyrolysis and sequential pot experiments were then conducted in Malaysia on three degraded soils. We first evaluated the effect of Leucaena biochar on yields of Amaranthus, a leafy vegetable crop and measured changes to soil pH and nutrient availability over two growth cycles. We then tested whether any yield response to biochar was dependent upon the rate of biochar or fertilizer application. We found that biochar application at 30 t ha −1 with maximal fertilizer increased yields between 17 and 53% on very strongly acidic soil. Biochar added at 15 t ha −1 with maximal fertilizer increased yield by 54% on strongly acidic soil whilst there was no significant yield response on fertilized, slightly acidic soil. Unfertilized biochar treatments showed small yield responses across all soils over 2 growth cycles (9–11%), but yields were much lower than in fertilized treatments. Biochar also decreased short-term N availability when applied with fertilizers, which may improve nitrogen retention and substantially increased soil pH. This may reduce mobility of Fe, Mn and Al ions, which were negatively associated with yield. Our results suggest that Leucaena biochar can elicit a positive crop yield response but only when combined with fertilizer additions on very strongly to strongly acidic tropical soils. Highlights: Low cost Leucaena biochar improved crop yield only on very acidic tropical soils. Biochar reduced short term soil N availability, potentially improving N retention. Increased yield was associated with high soil Mg and low Fe, Mn and Al availability.